2021
DOI: 10.3892/ol.2021.12613
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib induces apoptosis of human colorectal cancer cells by downregulating the JAK1/2‑STAT1‑Mcl‑1 axis

Abstract: Under pathological conditions, the Janus kinase (JAK)/STAT signaling pathway can regulate the proliferation, differentiation and migration of tumor cells, including colorectal cancer (CRC). CRC is the third major types of cancer among males and the second among females worldwide. In China, CRC is the fifth common cancer among both males and females. Western blotting, flow cytometry, RNA interference, immunoprecipitation, xenografts models, and immunohistochemical staining were carried out to evaluate the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…For WGD in COAD, bosutinib and ruxolitinib were suggested to target PLK1 kinase, a pivotal regulator of mitotic events frequently overexpressed in colon cancers 55–58 . These drugs have been reported to induce apoptosis in colon cancer cells 59,60 . Sunitinib was recommended as the most suitable drug for BRCA patients with WGD, supported by its efficacy in BRCA reported in some studies 61,62 , although caution is advised when applying it to metastatic breast cancer patients 63 .…”
Section: Resultsmentioning
confidence: 99%
“…For WGD in COAD, bosutinib and ruxolitinib were suggested to target PLK1 kinase, a pivotal regulator of mitotic events frequently overexpressed in colon cancers 55–58 . These drugs have been reported to induce apoptosis in colon cancer cells 59,60 . Sunitinib was recommended as the most suitable drug for BRCA patients with WGD, supported by its efficacy in BRCA reported in some studies 61,62 , although caution is advised when applying it to metastatic breast cancer patients 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that immune checkpoints such as PD-1, CTLA-4 and LAG-3 are upregulated on the surface of T cells in breast tumor tissues. The epigenetic modifications behind their upregulation are depends on the methylation of DNA and the distribution of inhibitory histone [28]. Therefore, the combination of targeted drugs and STAT1 blocking function is a new strategy for the treatment of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In rheumatoid arthritis, continuous activation of JAK signaling in synovial joints results in the most pronounced “apoptosis resistance” in apoptotic chondrocytes ( Malemud, 2018 ). Tofacitinib or ruxolitinib, JAK small molecule inhibitor, downregulated myeloid cell leukemia-1 mRNA level and decreased its protein level, which enabled BAK to trigger necroptosis ( Thapa et al, 2013 ; Li et al, 2021 ). Therefore, we speculate that the JAK1 is associated with the negative regulation of necroptosis in ICM.…”
Section: Discussionmentioning
confidence: 99%